In Vitro and In Vivo evaluations of Smilax myosotiflora (Ubi Jaga) compared to the well-known aphrodisiac plant of Eurycoma longifolia (Tongkat Ali) - Sharifah Aminah, Tuan Said; Jaya Vejayan, Palliah; Fatinah, Ahmad; Srikumar, Chakravarthi (Faculty of Pharmacy, University of Benin, 2024)
Smilax myosotiflora and Eurycoma longifolia are recognized as aphrodisiac medicinal plants in Malaysia. E. longifolia is widely purchased and extensively studied for its aphrodisiac effects, unlike S. myosotiflora. There has been some uncertainty regarding whether S. myosotiflora is comparable to E. longifolia in its aphrodisiac properties. In this study, both plants were extracted using a water distillation method under reflux, followed by clarification, freeze-drying, and yield comparison. The extracts were then subjected to in vitro experiments using TM-3 Leydig cell cultures. In vivo experiments involving mice were administered oral doses of 6 mg of each extract twice daily for 20 days. The results indicated that the extraction yield for E. longifolia was higher at 7.43% (w/w) compared to 5.06% (w/w) for S. myosotiflora. In the in vitro experiments, Leydig testicular cells treated with 50 μg/mL of E. longifolia for 72 hours exhibited an 83.93% increase in testosterone concentrations compared to untreated controls. Additionally, testosterone levels increased by 94.61% in mice treated with E. longifolia compared to control mice. However, no increase in testosterone was reported in either the in vitro or in vivo experiments conducted with S. myosotiflora. Both S. myosotiflora and E. longifolia were confirmed to enhance libido, as indicated by increased frequencies of mounting and intromission in pairing experiments with treated males and females. In conclusion, while both plants can enhance libido, S. myosotiflora did not demonstrate the ability to boost testosterone during the short duration of the treatments.